Phase-selective degree of hydration at setting: An in situ synchrotron diffraction study - Morales-Cantero, Alejandro; Cuesta-García, Ana María; Santacruz-Cruz, María Isabel; García-Aranda, Miguel Ángel; Gómez-de-la-Torre, María de los Ángeles (Elsevier, 2022)
Setting of Portland cements is still not well understood. Previous studies used techniques that analyse the pastes as a whole to correlate setting times with degree of hydration. Here, in-situ synchrotron X-ray diffraction analysed by the Rietveld method, with internal standard methodology, is used to derive alite dissolution rate and the crystallization kinetics of ettringite and portlandite in three commercial cements. Moreover, C–S–H gel precipitation pace has also been determined. C–S–H gel precipitation is key to account for setting. For grey Portland cements with w/c = 0.5, initial setting is attained when alite degree of hydration is close to 20% and the C–S–H gel content reached approximately 6 vol%.
Keywords: Cemento Portland; Cinética química; Portland cements; Hydration kinetics; Early age hydration measurements; Synchrotron radiation; Amorphous quantification